2014
DOI: 10.1246/cl.140648
|View full text |Cite
|
Sign up to set email alerts
|

A Superhydrophobic Copper Mesh with Microrod Structure for Oil–Water Separation Inspired from Ramee Leaf

Abstract: It is well known that superhydrophobic surfaces with unitary microstructures (such as the lotus leaf) have better surface mechanical properties than those with binary micro-and nanostructures (such as the ramee leaf). Rodlike unitary structured films are fabricated on copper meshes via a facile and simple chemical vapor corrosion method. Following the surface modification of 1-decanethiol (C 10 H 22 S), the resultant films exhibiting superhydrophobicity and superoleophilicity can be applied to separate the oil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Although great progress has been made in the preparation of superhydrophobic ENMs via generating a hierarchical structure, the laundering durability of such superhydrophobic membranes in cross-flow operations remains a concern due to the weak adhesion between the nanofibers and nanopartilces. It has been reported that superhydrophobic surfaces with unitary microstructures such as the ramee leaves possess better mechanical properties than those with binary micro- and nanostructures. Herein, we describe a new strategy to fabricate ENMs with robust superhydrophobicity by mimicking the unitary microstructures of ramee leaves via eletrospinning of poly­(vinyl alcohol) (PVA), followed by chemical cross-linking and surface fluorination. PVA has been selected as the membrane material with respect to its inexpensive cost, excellent chemical stability, and functional hydroxyl groups .…”
Section: Introductionmentioning
confidence: 99%
“…Although great progress has been made in the preparation of superhydrophobic ENMs via generating a hierarchical structure, the laundering durability of such superhydrophobic membranes in cross-flow operations remains a concern due to the weak adhesion between the nanofibers and nanopartilces. It has been reported that superhydrophobic surfaces with unitary microstructures such as the ramee leaves possess better mechanical properties than those with binary micro- and nanostructures. Herein, we describe a new strategy to fabricate ENMs with robust superhydrophobicity by mimicking the unitary microstructures of ramee leaves via eletrospinning of poly­(vinyl alcohol) (PVA), followed by chemical cross-linking and surface fluorination. PVA has been selected as the membrane material with respect to its inexpensive cost, excellent chemical stability, and functional hydroxyl groups .…”
Section: Introductionmentioning
confidence: 99%
“…The butterfly wings are composed of oriented micron scales and nano-strips F I G U R E 3 Natural Superhydrophobic surfaces (SHSs) with isotropic structures. (a) Ramie leaves [6]. (b) Chinese watermelon [7].…”
Section: Superhydrophobic Surfaces With Anisotropic Structuresmentioning
confidence: 99%
“…The pine-cone-like hierarchical micro-nanostructure [23], the surface distributed grooves and ridges in micrometer scale and many nano-wrinkles [24], and the unique nanoworm-like structure [25] were mainly modified by fluorosilane previously. Also, some other examples involve rodlike nanostructures of Cu(OH) 2 [26,27], highly dense ordered Cu 2 O nanorods [28], flower-like [29], leaves-like, and wormlike micro-/nano-scale structures [30,31], and these hydrophobic surfaces were finally modified by n -alkanethiolates [32]. To some extent, the techniques described above were efficient for separating mixtures of water and oil, however, there are some disadvantages that need to be overcome, such as time-consuming and complicated fabrication, special equipment, and expensive materials.…”
Section: Introductionmentioning
confidence: 99%